TEACHER TRAINING AND QOM LANGUAGE RECLAIM: THE CASE OF STUDENTS FROM COLONIA ABORIGEN - Lucía Romero Massobrio (Universidad Nacional del Nordeste, 2016)
In Chaco province, bilingual intercultural teachers have been trained during the last thirty years. Young people from the Qom, Wichi and Moqoit communities are been trained at CIFMA (Centro de Invetigación y Formación para la Modalidad Aborigen) as future teachers for EBI schools. This institution becomes a linguistic revitalization space for those who have diverse indigenous language competencies. In this paper, specifically we are interested in CIFMA students which came from Colonia Aborigen Chaco. This young people have limited skills in the language of their community. Based on the analysis of semistructured interviews and data provided by sociolinguistic questionnaires collected in CIFMA, we intend to explore the senses that this group builds around the Qom language, its "loss" and "reclaim". With this analysis, we intend to characterize the native category of "recuperantes" that the students use to describe themselves. Further, we will relate this category to other similar sociolinguistic categories, such as the "new European speakers" (Pujolar et al., 2015) and the "emergent bilinguals" of Peru (Zavala et al., 2014). As we will show, the "recuperantes" present specific features linked to the history of the Qom people and to the State's violence, and in relationship with the link between language revitalization and teacher training.